Self‐Supporting Metal–Organic Layers as Single‐Site Solid Catalysts. (8th March 2016) - Cao, Lingyun; Lin, Zekai; Peng, Fei; Wang, Weiwei; Huang, Ruiyun; Wang, Cheng; Yan, Jiawei; Liang, Jie; Zhang, Zhiming; Zhang, Teng; Long, Lasheng; Sun, Junliang; et al.
Abstract: Metal–organic layers (MOLs) represent an emerging class of tunable and functionalizable two‐dimensional materials. In this work, the scalable solvothermal synthesis of self‐supporting MOLs composed of [Hf6 O4 (OH)4 (HCO2 )6 ] secondary building units (SBUs) and benzene‐1, 3, 5‐tribenzoate (BTB) bridging ligands is reported. The MOL structures were directly imaged by TEM and AFM, and doped with 4′‐(4‐benzoate)‐(2, 2′, 2′′‐terpyridine)‐5, 5′′‐dicarboxylate (TPY) before being coordinated with iron centers to afford highly active and reusable single‐site solid catalysts for the hydrosilylation of terminal olefins. MOL‐based heterogeneous catalysts are free from the diffusional constraints placed on all known porous solid catalysts, including metal–organic frameworks. This work uncovers an entirely new strategy for designing single‐site solid catalysts and opens the door to a new class of two‐dimensional coordination materials with molecular functionalities.